The dynamics of public support for the king in Yogyakarta - Pajar Hatma Indra Jaya (Masyarakat, Kebudayaan dan Politik, 2018)
The background of this research is the support of the people of Yogyakarta to the sultan to lead Daerah Istimewa Yogyakarta. This paper is aimed at examining the relationship between a king and the community in the democracy era. The cases examined specifically in this study were the case of the proposed law of Yogyakarta in the Sutet region, and the ore mining case in Kulonprogo. Research was conducted qualitatively by collecting data through documentation, observation and interview. Informant retrieval technique is done by cluster technique. This research is analyzed by rational choice theory which assumes that people are always trying to optimize the choices that bring benefits (Mallarangeng 2008: 9, Kuper & Kuper 2000: 895). The study had various findings, such that public support of the king could not be explained by the concept of Javanese power and that logical consideration in the form of the interest proximity of each group becomes a concept of public support against the king. When the group interests are closer, they show their support, but, when the gap becomes wider, they readily change their support without fear of karma.